2023
DOI: 10.1088/1361-6528/acb943
|View full text |Cite
|
Sign up to set email alerts
|

Redox phase transformations in magnetite nanoparticles: impact on their composition, structure and biomedical applications

Abstract: Magnetite nanoparticles (NPs) are one of the most investigated nanomaterials so far and modern synthesis methods currently provide an exceptional control of their size, shape, crystallinity and surface functionalization. These advances have enabled their use in different fields ranging from environmental applications to biomedicine. However, several studies have shown that the precise composition and crystal structure of magnetite NPs depend on their redox phase transformations, which have a profound impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 212 publications
0
5
0
Order By: Relevance
“…Previous studies [82][83][84] have shown that redox processes occurring within the solid phase significantly influence both the nanostructure morphology and the Fe 3+ /Fe 2+ ratio. These complex processes include the redistribution of electron equivalents between the external surface and the bulk crystal structure of Fe 3 O 4 , as well as surface electron transfer from electrochemically active particles into the dissolved phase.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [82][83][84] have shown that redox processes occurring within the solid phase significantly influence both the nanostructure morphology and the Fe 3+ /Fe 2+ ratio. These complex processes include the redistribution of electron equivalents between the external surface and the bulk crystal structure of Fe 3 O 4 , as well as surface electron transfer from electrochemically active particles into the dissolved phase.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation and loss of magnetic properties are also common challenges that require a protective layer over bare IONPs. 37 …”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the reduction potentials for γ-Fe2O3 and δ-FeOOH (Fig. 6, Table 3) were quite similar, both at around -0.4 V. The studies of the authors (Lavorato et al 2023;Jungcharoen et al 2021;Jungcharoen et al 2022) explore the oxidation processes of Fe 2+ to Fe 3+ that affect the nanoparticle structure and the ratio of Fe 3+ to Fe 2+ within the crystal lattice. These studies show that stoichiometric magnetite is in equilibrium with dissolved Fe 2+ , prompting complex surface reactions, such as rapid atomic exchange, redistribution of electron equivalents between the bulk and the outermost surface of the particles, and surface electron transfer with redox particles in the solution (Jungcharoen et al 2021).…”
Section: Figmentioning
confidence: 94%